RANCANG BANGUN APLIKASI WEB UNTUK MENAJEMEN PROYEK BERBASIS SCRUM PADA PT. JOSE UPMIND DIGITAL OPTIMA - Fikri Mutaqin; Maulana Ardhiansyah (OKTAL : Jurnal Ilmu Komputer dan Sains, 2023)
Efforts to improve the performance of the team working on a particular project Software development with the Scrum framework is necessary. This is related with the increasing needs of the Team to make it easier and faster occupation. Scum framework has many components in it such as actors who play a role, events or activities that need to be done and artifacts that need to befulfilled. The Scrum Teamwork Management Information System was created to meet the needs and apply the Scrum framework in a system that computerized. The system is made using the prototyping method, and performs testing of multiple users who are already using the Scrum framework on his place of work. The results of the system test show the average percentage score.